Studi Komparasi Partisipasi Dalam Proses Perancangan Material Terbarukan - Eka Arifianty Puspita; Kahfiati Kahdar (JURNAL RUPA, 2021)
The participation approach has long been recognized in sustainable design projects. Some recent material innovations strive for demonstrating community participation in their design process to achieve a sustainable outcome. However, the terminology of participation can be perceived and implemented differently for actors involved in the process. Responding to the diverse understanding of participation, this paper tries to examine the implementation of participation in the making of two well-known renewable materials innovations, namely Totomoxtle and Pinatex. The methodology used in this research is a comparative descriptive which is analyzed through literature and comparative studies by referring to the ladder of participation theory by Arnstein, the form of participation by White, and the participation in design by Lee. Based on the analysis, there are different levels of participation held by actors and also various forms of participation occur in the design process. Moreover, the comparative studies also show that the actors who occupy a similar level of participation do not directly comprise a similar form and function of participation. However, the diverse forms and levels of participation in sustainable innovation establish a different type of relation and space for interaction between designers and other actors involved.